Computer software (SiD) assisted real-time single sperm selection associated with fertilization and blastocyst formation. Issue 4 (October 2022) - Mendizabal-Ruiz, Gerardo; Chavez-Badiola, Alejandro; Aguilar Figueroa, Isaac; Martinez Nuño, Vladimir; Flores-Saiffe Farias, Adolfo; Valencia-Murilloa, Roberto; Drakeley, Andrew; Garcia-Sandoval, Juan Paulo; Cohen, Jacques
Abstract: Research question: Is it possible to explore an association between individual sperm kinematics evaluated in real time and spermatozoa selected by an embryologist for intracytoplasmic sperm injection (ICSI), with subsequent normal fertilization and blastocyst formation using a novel artificial vision-based software (SiD V1.0; IVF 2.0, UK)? Design: ICSI procedures were randomly video recorded and subjected to analysis using SiD V1.0, proprietary software developed by our group. In total, 383 individual spermatozoa were retrospectively analysed from a dataset of 78 ICSI-assisted reproductive technology cycles. SiD software computes the progressive motility parameters, straight-line velocity (VSL) and linearity of the curvilinear path (LIN), of each sperm trajectory, along with a quantitative value, head movement pattern (HMP), which is an indicator of the characteristics of the sperm head movement patterns. The mean VSL, LIN and HMP measurements for each set of spermatozoa were compared based on different outcome measures. Results: Statistically significant differences were found in VSL, LIN and HMP among those spermatozoa selected for injection ( P < 0.001). Additionally, LIN and HMP were found to be significantly different between successful and unsuccessful fertilization ( P  = 0.038 and P  = 0.029, respectively). Additionally, significantly higher SiD scores were found for those spermatozoa that achieved both successful fertilization ( P  = 0.004) and blastocyst formation ( P  = 0.013). Conclusion: The possibility of carrying out real-time analyses of individual spermatozoa using an automatic tool such as SiD creates the opportunity to assist the embryologist in selecting the better spermatozoon for injection in an ICSI procedure.